Psicopatología y agresión en la población penitenciaria ecuatoriana - Peralta, Fabricio H. (2020)
Sentences deprived of liberty and security measures in the field of social rehabilitation must be oriented, as a primary objective, towards the re-education and full reintegration of the individual into society.